Battery monomer, negative electrode active material, preparation method of negative electrode active material, battery and electric device
By using a cladding with oxygen-containing functional groups in the negative electrode active material of lithium-ion batteries, the fast charging performance of graphite materials is improved, and the bottleneck of improving the fast charging performance of lithium-ion batteries is solved.
Patent Information
- Application Number
- CN202510124956.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are bottlenecks in improving the fast charging performance of existing lithium-ion batteries, especially the intrinsic fast charging capability of graphite materials.
A negative electrode active material is used, which consists of graphite as the core, and the cladding layer includes carbon and oxygen-containing functional groups, and the content of oxygen-containing functional groups is 20% to 70%. A cladding layer is formed by mixing a coating agent containing oxygen-containing functional groups with graphite and carbonizing it.
By increasing the disorder of the cladding layer, the fast charging performance of the battery is significantly improved, and the diffusion rate and electrochemical performance of lithium ions are improved.
Smart Images

Figure CN119890412A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a battery cell, a negative electrode active material and a preparation method thereof, a battery, and an electrical device. Background Art
[0002] As an emerging sustainable energy storage technology, lithium-ion batteries have the characteristics of low cost and environmental friendliness, so their application has been increasingly developed in recent years.
[0003] Therefore, higher requirements are placed on the fast charging performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of the present application is to provide a battery cell, a negative electrode active material and a preparation method thereof, a battery, and an electrical device.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, an embodiment of the present application provides a battery cell, including:
[0007] A negative electrode sheet, the negative electrode sheet comprising a negative electrode film layer;
[0008] The negative electrode film layer includes a negative electrode active material; the negative electrode active material includes a core and a coating layer;
[0009] The inner core is graphite; the coating layer includes carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass.
[0010] In the above technical solution, the negative electrode active material includes a core and a coating layer, the core is graphite; the coating layer includes carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass; relative to conventional carbon-coated graphite (whose oxygen-containing functional group content is extremely low and almost zero), the content of oxygen-containing functional groups in the negative electrode active material is 20% to 70%. The increase in the content of oxygen-containing functional groups can increase the disorder of the coating layer, which is beneficial to improving the fast charging performance of the battery.
[0011] In some embodiments, in the negative electrode active material, the content of the oxygen-containing functional groups is 22% to 52% by mass.
[0012] In some embodiments, the oxygen-containing functional group includes at least one of a hydroxyl group, a carbonyl group, a carboxyl group, or an epoxy group.
[0013] In some embodiments, the oxygen content of the negative electrode active material is 0.2%-1% by mass;
[0014] In some embodiments, the negative electrode active material has an oxygen content of 0.57%-0.77% by mass.
[0015] In some embodiments, the median of the Raman value ID / IG of the negative electrode active material is denoted as R 50 ; R 50 0.15~0.40; R 50 The test method is: use high-precision Renishaw confocal Raman test equipment to perform a full-scale scan of the surface of the negative electrode active material, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, and the Raman value ID / IG corresponding to the 50% ranking is defined as R50;
[0016] In some embodiments, the Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; (R90-R10) / R50 is 0.13-0.25; the testing method of R90, R10 and R50 is: use a high-precision Renishaw confocal Raman testing device to perform a full-scale scan of the surface of the negative electrode active material, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, and the Raman value ID / IG corresponding to the 10% ranking is defined as R10, the Raman value ID / IG corresponding to the 50% ranking is defined as R50, and the Raman value ID / IG corresponding to the 90% ranking is defined as R90.
[0017] In some embodiments, the portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as the uncoated portion; based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; X≤10%; and X is 3.22% to 10%.
[0018] In a second aspect, an embodiment of the present application provides a negative electrode active material, the negative electrode active material comprising a core and a coating layer;
[0019] The inner core is graphite; the coating layer comprises carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass.
[0020] In some embodiments, the negative electrode active material satisfies at least one of the following characteristics:
[0021] (1) In the negative electrode active material, the content of oxygen-containing functional groups is 0.22% to 0.52% by mass;
[0022] (2) In the negative electrode active material, the oxygen-containing functional group includes at least one of a hydroxyl group, a carbonyl group, a carboxyl group or an epoxy group;
[0023] (3) The oxygen content in the negative electrode active material is 0.2% to 1% by mass;
[0024] (4) The median of the Raman value ID / IG of the kernel is denoted as R 50 ; R of the kernel 50 is 0.06 to 0.1; the R50 test method of the kernel is: use a high-precision Renishaw confocal Raman test device to perform an all-round scan on the material surface, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% sorting is defined as R50;
[0025] (5) The median of the Raman value ID / IG of the negative electrode active material is denoted as R 50 ; R of negative electrode active material 50 The R50 test method is as follows: use high-precision Renishaw confocal Raman test equipment to perform a full-scale scan of the material surface, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the corresponding Raman data obtained from scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% ranking is defined as R50;
[0026] (6) The Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; (R90-R10) / R50 is 0.13-0.25; the test method of R90, R10 and R50 is: use a high-precision Renishaw confocal Raman test device to perform a full-scale scan of the material surface, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 10% ranking is defined as R10, the Raman value corresponding to the 50% ranking is defined as R50, and the Raman value corresponding to the 90% ranking is defined as R90;
[0027] (7) The portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as the uncoated portion; based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; and X is 3.22% to 10%.
[0028] In a third aspect, the present application provides a method for preparing a negative electrode active material, comprising:
[0029] A coating agent containing oxygen-containing functional groups and a core are prepared into a mixed solution;
[0030] The mixed solution is carbonized to form a coating layer; the inner core is graphite; the coating layer comprises carbon and oxygen-containing functional groups; in terms of mass percentage, the content of the oxygen-containing functional groups is 20% to 70% of the total mass of the coating layer and the inner core.
[0031] In the above technical scheme, a coating agent containing oxygen-containing functional groups and a core are made into a mixed solution, so that the coating agent containing oxygen-containing functional groups can fully and evenly infiltrate the core, which is beneficial to improve the uniformity of subsequent coating; the mixed solution is carbonized to form a coating layer, and the content of the oxygen-containing functional groups is 20% to 70% of the total mass of the coating layer and the core; compared with conventional carbon-coated graphite, the content of oxygen-containing functional groups in the negative electrode active material is greatly increased; the increase in the content of oxygen-containing functional groups can increase the disorder of the coating layer, which is beneficial to improve the fast charging performance of the battery.
[0032] In some embodiments, the content of oxygen-containing functional groups in the capping agent containing oxygen-containing functional groups is 1%-5% based on the total mass of the capping agent.
[0033] In some embodiments, preparing a capping agent comprising an oxygen-containing functional group comprises:
[0034] Using an oxidant to react with a carbon coating agent;
[0035] Optionally, the oxidant includes: at least one of an acidic substance or an alkaline substance; Optionally, the acidic substance includes: at least one of nitric acid, sulfuric acid, hydrogen peroxide or potassium permanganate; Optionally, the alkaline substance includes: at least one of sodium hydroxide or potassium hydroxide; Optionally, the carbon coating agent includes: a copolymer or an organic polymer composite material; Optionally, the carbon coating agent includes: at least one of asphalt, sucrose or glucose;
[0036] Optionally, the content of the oxidant is 1% to 10% of the mass of the carbon coating agent.
[0037] In some embodiments, a coating agent containing oxygen-containing functional groups and a core are prepared into a mixed solution, comprising:
[0038] mixing a carbon coating agent solution with the core;
[0039] Optionally, preparing the carbon coating agent solution comprises:
[0040] Mixing surfactant, water and carbon coating agent at 50°C to 60°C;
[0041] Optionally, the surfactant includes: anionic surfactant; Optionally, the surfactant includes: sodium dodecyl sulfate.
[0042] In some embodiments, carbonizing the mixed solution comprises:
[0043] When the coating agent solution is mixed with the core, the concentration of the coating agent solution is 1% to 10% by mass percentage;
[0044] Optionally, the carbonization temperature is 700°C to 1300°C.
[0045] In some embodiments, the preparation method further comprises:
[0046] The product obtained by carbonization is subjected to oxidation treatment;
[0047] Optionally, the oxidation treatment includes: reacting the product obtained by carbonization with an oxidant.
[0048] In a fourth aspect, an embodiment of the present application provides a battery, the battery comprising a battery cell provided by any of the aforementioned embodiments.
[0049] In a fifth aspect, an embodiment of the present application provides an electrical device, the electrical device comprising a battery provided by any of the aforementioned implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0052] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0053] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0054] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0055] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0056] Figure 6 Schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.
[0057] icon:
[0058] 110 first area; 120 second area; 130 pole ear; 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0059] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0061] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0062] In the description of the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "inside" and "outside" are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.
[0063] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.
[0064] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0065] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of the present application shown in the drawings, as well as the overall heights, lengths, widths, and other dimensions of the integrated device are only exemplary descriptions and should not constitute any limitation to the present application.
[0066] At present, the demand for fast charging capability of batteries is getting higher and higher, which poses a challenging goal for the intrinsic fast charging capability of graphite. The modification of traditional graphite focuses on the selection of coke, aggregate control, particle size control, and the control of the coating amount of the coating layer; however, this control has reached its limit, and the continued improvement of fast charging performance has reached a bottleneck.
[0067] Based on this, refer to Figure 1 In a first aspect, the present application provides a battery cell, including:
[0068] A negative electrode sheet, the negative electrode sheet comprising a negative electrode film layer;
[0069] The negative electrode film layer includes a negative electrode active material; the negative electrode active material includes a core and a coating layer;
[0070] The inner core is graphite; the coating layer comprises carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass.
[0071] In the above technical solution, the negative electrode active material includes a core and a coating layer, the core is graphite; the coating layer includes carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass. Compared with conventional carbon-coated graphite (whose oxygen-containing functional group content is extremely low or almost zero), the content of oxygen-containing functional groups in the negative electrode active material is 70% to 70%. The increase in oxygen-containing functional groups can increase the disorder of the coating layer, which is beneficial to improving the fast charging performance of the battery.
[0072] In some embodiments of the present application, the battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet includes a positive current collector and a positive electrode film layer; the negative electrode sheet includes a negative current collector and a negative electrode film layer; during the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0073] Further optionally, in some embodiments of the present application, the content of oxygen-containing functional groups in the negative electrode active material is 22% to 52%.
[0074] In the above technical solution, by controlling the content of oxygen-containing functional groups in the negative electrode active material to 22% to 52% by mass, the disorder of the coating layer can be further improved, which is beneficial to improving the fast charging performance of the battery.
[0075] Illustratively, in some embodiments of the present application, in the above-mentioned negative electrode active material, the content of oxygen-containing functional groups, measured by mass percentage, is 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70% or a range between any two of the foregoing values.
[0076] Furthermore, in some embodiments of the present application, the oxygen-containing functional group includes at least one of a hydroxyl group (—OH), a carbonyl group (C═O), a carboxyl group (—COOH), or an epoxy group (—COC—).
[0077] Illustratively, in some embodiments of the present application, the oxygen-containing functional group is any one of a hydroxyl group (-OH), a carbonyl group (C=O), a carboxyl group (-COOH) or an epoxy group (-COC-); or in some embodiments of the present application, the oxygen-containing functional group is a hydroxyl group (-OH) and a carbonyl group (C=O); or in some embodiments of the present application, the oxygen-containing functional group is a carboxyl group (-COOH) and an epoxy group (-COC-); or in some embodiments of the present application, the oxygen-containing functional group is a hydroxyl group (-OH), a carbonyl group (C=O), a carboxyl group (-COOH) and an epoxy group (-COC-).
[0078] Furthermore, in some embodiments of the present application, in the negative electrode active material, the oxygen content is 0.2%-1% by mass.
[0079] In the above technical solution, by controlling the oxygen content in the negative electrode active material to be 0.2%-1% by mass, the disorder of the coating layer can be increased, which is beneficial to improving the fast charging performance of the battery.
[0080] Illustratively, in some embodiments of the present application, in the coating layer, the oxygen content, by mass percentage, is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range between any two of the foregoing values.
[0081] Further optionally, in some embodiments of the present application, in the negative electrode active material, the oxygen content is 0.57%-0.77% by mass.
[0082] Furthermore, in some embodiments of the present application, the median Raman value ID / IG of the negative electrode active material is recorded as R50; R50 is 0.15-0.40; the testing method of R50 is: use a high-precision Renishaw confocal Raman testing device to perform a full-scale scan of the surface of the negative electrode active material, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, and the Raman value ID / IG corresponding to the 50% ranking is defined as R50.
[0083] Illustratively, in some embodiments of the present application, the above-mentioned R50 is 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40 or the range between any two of the foregoing values.
[0084] Further optionally, the Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; (R90-R10) / R50 is 0.13-0.25; the test method of R90, R10 and R50 is: use high-precision Renishaw confocal Raman testing equipment to perform a full-scale scan of the surface of the negative electrode active material, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, and the Raman value ID / IG corresponding to the 10th% ranking is defined as R10, the Raman value ID / IG corresponding to the 50th% ranking is defined as R50, and the Raman value ID / IG corresponding to the 90th% ranking is defined as R90.
[0085] Illustratively, in some embodiments of the present application, (R90-R10) / R50 is 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25 or a range between any two of the foregoing values.
[0086] Furthermore, in some embodiments of the present application, the portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as the uncoated portion; based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; and X is 3.22% to 10%.
[0087] Illustratively, in some embodiments of the present application, based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is denoted by X; X is 3.22%, 3.30%, 3.35%, 3.40%, 3.45%, 3.50%, 3.55%, 3.60%, 3.65%, 3.70%, 3.75%, 5.00%, 6.50%, 7.00%, 8.50%, 9.00%, 9.50%, 10% or a range between any two of the foregoing values.
[0088] In some embodiments of the present application, the test method for the proportion of the uncoated portion of the above-mentioned negative electrode active material is:
[0089] The surface of the negative electrode active material was scanned in all directions using high-precision Renishaw confocal Raman testing equipment. The scanning area was 100*100 microns, the step length was 2 microns, and the total number of scanning points was 2500. The Raman values ID / IG corresponding to the 2500 scanned points were calculated, and the proportion of ID / IG≤0.1 in the total number of measurements was counted.
[0090] Some embodiments of the present application provide a negative electrode active material, the negative electrode active material comprising a core and a coating layer;
[0091] The inner core is graphite; the coating layer comprises carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass.
[0092] Furthermore, in some embodiments of the present application, the negative electrode active material satisfies at least one of the following characteristics:
[0093] (1) In the negative electrode active material, the content of oxygen-containing functional groups is 0.22% to 0.52% by mass.
[0094] (2) In the negative electrode active material, the oxygen-containing functional group includes at least one of a hydroxyl group (-OH), a carbonyl group (C=O), a carboxyl group (-COOH) or an epoxy group (-COC-).
[0095] (3) The oxygen content in the negative electrode active material is 0.2%-1% by mass.
[0096] (4) The median of the Raman value ID / IG of the kernel is denoted as R 50 ; R of the kernel 50is 0.06 to 0.1; the R50 test method of the kernel is: use a high-precision Renishaw confocal Raman test device to perform an all-round scan on the material surface, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% sorting is defined as R50;
[0097] (6) The median of the Raman value ID / IG of the negative electrode active material is denoted as R 50 ; R of negative electrode active material 50 The R50 test method is as follows: use high-precision Renishaw confocal Raman test equipment to perform a full-scale scan of the material surface, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the corresponding Raman data obtained from scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% ranking is defined as R50;
[0098] (7) The Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; (R90-R10) / R50 is 0.13-0.25; the test method of R90, R10 and R50 is: use a high-precision Renishaw confocal Raman test device to perform a full-scale scan of the material surface, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 10% ranking is defined as R10, the Raman value corresponding to the 50% ranking is defined as R50, and the Raman value corresponding to the 90% ranking is defined as R90;
[0099] (8) The portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as the uncoated portion; based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; and X is 3.22% to 10%.
[0100] Some embodiments of the present application provide a method for preparing a negative electrode active material, comprising:
[0101] A coating agent containing oxygen-containing functional groups and a core are prepared into a mixed solution;
[0102] The mixed solution is carbonized to form a coating layer; the core is graphite; the coating layer includes carbon and oxygen-containing functional groups; in terms of mass percentage, the content of the oxygen-containing functional groups is 20% to 70% of the total mass of the coating layer and the core.
[0103] In the above technical scheme, a coating agent containing oxygen-containing functional groups and a core are made into a mixed solution, so that the coating agent containing oxygen-containing functional groups can fully and evenly infiltrate the core, which is beneficial to improve the uniformity of subsequent coating; the mixed solution is carbonized to form a coating layer, and the content of the oxygen-containing functional groups is 20% to 70% of the total mass of the coating layer and the core; relative to conventional carbon-coated graphite, the content of oxygen-containing functional groups in the negative electrode active material is greatly increased, and the increase in the content of oxygen-containing functional groups can improve the disorder of the coating layer, which is beneficial to improve the fast charging performance of the battery.
[0104] Furthermore, in some embodiments of the present application, based on the total mass of the coating agent, the content of oxygen-containing functional groups in the coating agent containing oxygen-containing functional groups is 0.2% to 1% by mass.
[0105] Further, in some embodiments of the present application, preparing a capping agent containing oxygen-containing functional groups comprises:
[0106] An oxidant is used to react with the carbon coating agent.
[0107] Further, in some embodiments of the present application, the oxidant includes: at least one of an acidic substance or an alkaline substance; optionally, the acidic substance includes: at least one of nitric acid, sulfuric acid, hydrogen peroxide or potassium permanganate; optionally, the alkaline substance includes: at least one of sodium hydroxide or potassium hydroxide; the carbon coating agent includes: a copolymer or an organic polymer composite material; optionally, the carbon coating agent includes: at least one of asphalt, sucrose or glucose.
[0108] Illustratively, in some embodiments of the present application, the above-mentioned oxidant is selected from any one of nitric acid, sulfuric acid, sodium hydroxide or potassium hydroxide; or in some embodiments of the present application, the above-mentioned oxidant is selected from a mixture of nitric acid, sulfuric acid, sodium hydroxide and potassium hydroxide; or in some embodiments of the present application, the above-mentioned oxidant is selected from a mixture of nitric acid and sulfuric acid; or in some embodiments of the present application, the above-mentioned oxidant is selected from a mixture of sodium hydroxide and potassium hydroxide.
[0109] In the above technical scheme, the use of acidic or alkaline substances as oxidants can effectively change the chemical structure of the carbon coating agent, thereby introducing more polar groups (such as hydroxyl, carbonyl, carboxyl, etc.). These groups can improve the polarity of the carbon coating agent (such as asphalt) and its compatibility with other materials. At the same time, they can also change the softening point, viscosity and temperature sensitivity of the asphalt and other properties; it is beneficial to improve the coating effect.
[0110] Furthermore, in some embodiments of the present application, optionally, the content of the oxidant is 1% to 10% of the mass of the carbon coating agent.
[0111] Illustratively, in some embodiments of the present application, the content of the above-mentioned oxidant is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% of the mass of the carbon coating agent or a range between any two of the foregoing values.
[0112] Furthermore, in some embodiments of the present application, a coating agent containing oxygen-containing functional groups and a core are prepared into a mixed solution, comprising:
[0113] The carbon capping agent solution is mixed with the core.
[0114] Further optionally, in some embodiments of the present application, preparing the carbon coating agent solution comprises:
[0115] At 50°C to 60°C, mix the surfactant, water and carbon coating agent.
[0116] For example, in some embodiments of the present application, preparing a carbon coating agent solution comprises:
[0117] The surfactant, water and carbon coating agent are mixed at 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 60°C or in a range between any two of the foregoing values.
[0118] Further optionally, in some embodiments of the present application, the surfactant includes: anionic surfactant; optionally, the surfactant includes: sodium dodecyl sulfate.
[0119] The above technical solution selects an anionic surfactant whose HLB value (hydrophile-lipophile balance) is suitable for forming an oil-in-water emulsion; it is conducive to preparing a uniformly dispersed carbon coating agent solution.
[0120] Illustratively, in some embodiments of the present application, the above-mentioned surfactant is sodium dodecyl sulfate.
[0121] After being oxidized by acid and alkali, the carbon capping agent changes its chemical properties and forms more polar groups. These groups increase the interaction between the carbon capping agent (such as asphalt) and water, so that under high temperature, high pressure or the presence of surfactants, the oxidized capping agent (such as oxidized asphalt) may form a stable emulsion in water.
[0122] Illustratively, in some optional embodiments of the present application, the oxidized asphalt can be first heated to 100 to 120°C to reduce its viscosity, the surfactant can be dissolved in water, the water temperature can be maintained at 50 to 60°C, and the heated oxidized asphalt can be slowly added to the surfactant aqueous solution under high-speed stirring (stirring speed is about 1000 to 3000 rpm), and stirred for 10 to 30 minutes; to obtain a carbon coating agent solution.
[0123] Further, in some embodiments of the present application, carbonizing the mixed solution comprises:
[0124] When the coating agent solution is mixed with the inner core, the concentration of the coating agent solution is 1% to 10% by mass.
[0125] Illustratively, in some embodiments of the present application, the concentration of the coating agent solution is, by mass percentage, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 10% or a range between any two of the foregoing values.
[0126] Further optionally, in some embodiments of the present application, the carbonization temperature is 700°C to 1300°C.
[0127] Illustratively, in some embodiments of the present application, the carbonization temperature is 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C or a range between any two of the foregoing values.
[0128] Furthermore, in some embodiments of the present application, the preparation method further comprises:
[0129] The carbonized product is subjected to oxidation treatment.
[0130] Furthermore, in some embodiments of the present application, optionally, the oxidation treatment includes: reacting the product obtained by carbonization with an oxidant.
[0131] In the above technical solution, by reacting the product obtained by carbonization with an oxidant, the electronic conductivity and ionic conductivity of the coating layer can be further adjusted, the disorder of the coating layer can be increased, and the fast charging performance can be further improved.
[0132] Illustratively, in some embodiments of the present application, the aforementioned oxidant may be used to oxidize the product obtained by carbonization; illustratively: at least one of nitric acid, sulfuric acid, sodium hydroxide, and potassium hydroxide.
[0133] In the above technical solution, after the carbon coating agent is mixed with the inner core, the inner core is carbonized and coated on its surface. During the carbonization process, part of the oxygen is separated from the coating layer to form abundant oxygen vacancies; part of the oxygen remains in the coating layer in the form of oxygen-containing functional groups (in the form of CO or C=O, etc.); thus, an oxygen-rich coating layer is obtained.
[0134] The oxygen-rich coating layer induces the formation of SEI during the chemical film formation process, forming a SEI with more inorganic components - lithium oxide (Li 2 O), this inorganic component SEI is much stronger than the conventional component (Li 2 CO 3 On the other hand, this type of inorganic component SEI has a lower desolvation energy barrier, which accelerates the transfer of lithium ions in the coating layer and reduces the interface impedance Rct+Rf (Rct is the graphite desolvation energy barrier and Rf is the SEI part).
[0135] The oxygen-rich coating layer induces the formation of SEI during the chemical film formation process, forming a SEI with more inorganic components - lithium oxide (Li 2 O), SEI rich in such components is more stable, can better inhibit further decomposition of the electrolyte, reduce the occurrence of side reactions, and improve the cycle stability and safety of the battery;
[0136] At the same time, if a suitable process is adopted to control the uniform dispersion of O in the coating layer, the formed inorganic components will also be evenly dispersed in the SEI film, which will improve the uniformity of SEI and further improve the cycle performance and safety of the battery.
[0137] The oxygen-containing functional groups remaining after carbonization can increase the surface polarity and reactivity of the material, improve the wettability of the graphite material with the electrolyte, and increase the diffusion rate of lithium ions, thereby improving the electrochemical performance of the battery.
[0138] The formed coating layer containing oxygen vacancies is beneficial to the electronic and ionic conductivity of the negative electrode active material.
[0139] For electronic conductivity, on the one hand, oxygen vacancies can act as electron traps to capture free electrons, thereby reducing the electronic conductivity of the material. Electrons stay at oxygen vacancies, reducing the concentration of free electrons and hindering the flow of electrons. On the other hand, oxygen vacancies introduce defect states in the band structure, which can serve as additional carrier sources and increase the conductivity of the material. In some cases, these defect states can promote the hopping transmission of electrons and improve electronic conductivity.
[0140] For ionic conductivity, similar to electronic conductivity, oxygen vacancies can serve as adsorption and desorption sites for lithium ions. Lithium ions form coordination bonds with oxygen atoms near the oxygen vacancies, promoting the storage and release of lithium ions, thereby increasing the lithium ion transmission rate.
[0141] In summary, the presence of certain oxygen vacancies in oxidized asphalt is beneficial to accelerate the desolvation process and the diffusion process of the coating layer, thereby improving the fast charging performance.
[0142] Oxygen vacancies can increase the disorder of the coating layer. This increase in disorder is mainly due to the influence of oxygen vacancies on the structure of carbon materials, which is specifically manifested in the following aspects:
[0143] Introduction of structural defects: Oxygen vacancies, as structural defects, destroy the originally ordered graphite layer structure of carbon materials, resulting in an increase in disorder in local areas. This disorder can be manifested as distortion, breakage or rearrangement of the carbon layer, forming an amorphous or semi-crystalline structure.
[0144] Changes in electronic structure: The presence of oxygen vacancies changes the electronic structure of carbon materials and introduces defect states, which can act as electron traps or promote the hopping transport of electrons, further increasing the disorder of the material.
[0145] Changes in surface properties: Oxygen vacancies can change the chemical properties of the carbon material surface, such as increasing surface polarity or introducing new functional groups. These changes increase the complexity of the surface and lead to an increase in surface disorder.
[0146] In summary, this coating layer rich in polar oxygen functional groups and oxygen vacancies can regulate SEI to improve the diffusion process of lithium ions and the desolvation process to enhance the fast charging performance and wettability of the material; at the same time, the formed oxygen vacancies can not only regulate the electronic conductivity and ion conductivity of the coating layer, but also increase the disorder of the coating layer, further improving the fast charging performance.
[0147] In some embodiments of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector.
[0148] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0149] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0150] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), lithium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0151] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0152] In some embodiments, the negative electrode film layer may also optionally include other additives, such as a thickener (eg, carboxymethyl cellulose lithium (CMC-Li)).
[0153] In some embodiments, the film layer may further include a binder, which is used to fix the additive on the negative electrode plate. The type of the binder is not particularly limited, and those skilled in the art may flexibly select the binder according to actual needs.
[0154] [Positive electrode]
[0155] In some embodiments of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer formed on at least one surface of the positive electrode current collector.
[0156] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0157] In some optional embodiments of the present application, the above-mentioned positive electrode active material may include: a polyanion positive electrode material, a positive electrode material with a layered structure.
[0158] Further optionally, in some embodiments of the present application, the above-mentioned polyanion cathode material includes: LiMPO 4 , LiMPO 4 The M includes Mn and non-Mn elements, and the non-Mn elements include one or both of a first doping element and a second doping element. The first doping element is manganese doping, and the second doping element is phosphorus doping.
[0159] Furthermore, in some embodiments of the present application, the first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.
[0160] Furthermore, in some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N.
[0161] Further, in some embodiments of the present application, the second positive electrode active material includes: Li 1+x Mn 1-y A y P 1- z R z O 4 , wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
[0162] Further, in some embodiments of the present application, the second positive electrode active material includes: Li h A i Mn 1-j B j P 1- k C k O 4-l D l, wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; C includes one or more elements selected from the group consisting of B, S, Si, and N; D includes one or more elements selected from the group consisting of S, F, Cl, and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the second positive electrode active material is electrically neutral.
[0163] In the technical solutions of some embodiments of the present application, the compound Li 1+x Mn 1-y AHr 1-z R 4 The preparation method may include the following steps:
[0164] (1) dissolving a manganese source, a source of an element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with the element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with the element A;
[0165] (2) adding a lithium source, a phosphorus source, an element R source, a solvent, and the manganese salt doped with element A obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;
[0166] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;
[0167] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.
[0168] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.
[0169] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. The source of element R is selected from at least one of sulfate, borate, nitrate and silicate of element R. The source of element A is selected from at least one of simple substance, oxide, phosphate, oxalate, carbonate and sulfate of A.
[0170] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k Ck O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
[0171] It should be noted that Li h A i Mn 1-j B j P 1-k C k O 4-l D l The compound is actually a specific LiMPO 4 Materials. The preparation method can refer to Li 1+x Mn 1-y A y P 1-z R z O 4 , no limitation is made here.
[0172] In the technical solutions of some embodiments of the present application, the positive electrode active material also has a carbon-containing coating layer.
[0173] The introduction of a carbon-containing coating layer improves the conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually LiMPO 4 The core has a core-shell structure in which the surface of the core is covered with a coating layer.
[0174] In the technical solutions of some embodiments of the present application, the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material is 1% to 3%; illustratively, the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material is 1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or a range between any two of the foregoing values.
[0175] Furthermore, in some embodiments of the present application, the layered positive electrode material includes: a ternary layered structure system material.
[0176] Exemplarily, in some embodiments of the present application, the ternary layered structure system material includes: Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 includes one or both elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
[0177] Exemplarily, the ternary system material can be LiNi 0.4 Co 0.2 Mn 0.4 O 2 , LiNi 0.5 Co 0.2 Mn 0.3 O 2 and LiNi 0.7 Co 0.15 Mn 0.15 O 2 etc. In Li a Ni b Co c M1 d M2 e O f R g , a can be any one or more values within the range of 0.75 to 1.2, b can be any one or more values within the range of 0.3 to 1.0, c can be any one or more values within the range of 0 to 0.4, d can be any one or more values within the range of 0 to 1, e can be any one or more values within the range of 0 to 0.2, f can be any value within the range of 1 to 2.5, and g can be any one or more values within the range of 0 to 1.
[0178] Optionally, in the technical solutions of some embodiments of the present application, the positive electrode active material includes nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials. Among them, the ternary system materials include nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials.
[0179] It should be noted that in the enumeration of the positive electrode active material in the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. When the positive electrode active material is applied to the battery system, the molar content of Li will change after charge and discharge cycles.
[0180] In addition, due to the different preparation processes and conditions of the materials, the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y A y P 1-z R z O 4 The molar content of the oxygen element is not strictly 4.
[0181] For example, the positive electrode active material may be LiFePO 4 、LiMn 0.1 Fe 0.9 PO 4 、LiMn 0.2 Fe 0.8 PO 4 、LiMn 0.3 Fe 0.7 PO 4 、LiMn 0.4 Fe 0.6 PO 4 、LiMn 0.5 Fe 0.5 PO 4 、LiMn 0.6 Fe 0.4 PO 4 、LiMn 0.7 Fe 0.3 PO 4 、LiMn 0.8 Fe 0.2 PO 4 、LiMn 0.9 Fe 0.1 PO 4 、LiMnPO 4 、LiMn 0.5 Al 0.5 P 0.5 B 0.5 O 4 、LiMn 0.5 Mg 0.5 P 0.5 S 0.5 O 4 wait,
[0182] Further optionally, in some embodiments of the present application, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0183] Further optionally, in some embodiments of the present application, the conductive agent in the positive electrode film layer may include porous carbon materials and non-porous carbon materials; illustratively, the porous carbon materials include: activated carbon, etc.; the non-porous carbon materials include: at least one of acetylene black, carbon black, carbon nanotubes, graphene or carbon nanofibers.
[0184] Further optionally, in some embodiments of the present application, the amount of the conductive agent added to the positive electrode slurry is 1% to 5% by mass. Exemplarily, the amount of the conductive agent added to the positive electrode slurry is 1%, 1.1%, 1.2%, 1.5%, 1.8%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.5%, 3.8%, 4%, 4.1%, 4.5%, 4.8%, 5% or the range between any two of the foregoing values.
[0185] In some embodiments of the present application, the positive electrode slurry prepared as above is coated on at least one surface of a positive electrode current collector, and after drying, cold pressing and other processes, a positive electrode sheet can be obtained.
[0186] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0187] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0188] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0189] [Electrolytes]
[0190] The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). Battery cells using electrolytes, and some battery cells using solid electrolytes.
[0191] The electrolyte conducts ions between the positive electrode and the negative electrode.
[0192] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0193] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0194] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0195] [Isolation film]
[0196] In some embodiments, the present application has no particular limitation on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0197] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0198] In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly 52 through a winding process or a lamination process.
[0199] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0200] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0201] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0202] In some embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0203] Some embodiments of the present application provide a battery, comprising a battery cell provided by any of the aforementioned embodiments.
[0204] In the above technical solution, the term "battery" may refer to at least one of a battery cell, a battery module or a battery pack.
[0205] For example, in some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0206] Figure 3 5 is an example of a battery module. Figure 3In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0207] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0208] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0209] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0210] Some embodiments of the present application provide an electrical device, which includes the battery cell provided by any of the aforementioned embodiments, or the electrical device includes the battery provided by any of the aforementioned embodiments.
[0211] The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0212] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0213] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the battery, a battery pack or a battery module can be used.
[0214] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery may be used as a power source.
[0215] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0216] Example 1
[0217] A battery cell is provided, which is prepared according to the following steps:
[0218]
Negative electrode sheet preparation
[0219] 1. Preparation of negative electrode active materials
[0220] (1) Mix the coating agent (asphalt) and the oxidant (nitric acid) to obtain a mixture; the mass concentration of nitric acid is 10%, and the amount of nitric acid added is 9% of the weight of the asphalt. Heat and stir the mixture at 100°C to carry out an oxidation reaction. After the reaction is completed, use an alkali to neutralize the excess acid, and then wash with water to remove the residual oxidant and by-products. Finally, the oxidized asphalt is dried and subjected to necessary treatment to remove moisture and impurities to obtain oxidized asphalt. The oxygen content in the treated coating agent accounts for 4.23% by mass.
[0221] The oxidized asphalt is heated to 100 to 120°C, sodium dodecyl sulfate (SDS) is dissolved in water, the water temperature is maintained at 60°C, and the heated oxidized asphalt is slowly added to the surfactant aqueous solution under high-speed stirring at 3000 rpm, and stirred for 10 minutes to obtain a coating agent solution. The concentration of the surfactant is 1% of the total mass of the oxidized asphalt.
[0222] The coating agent solution and the core (graphite) were mixed at room temperature and stirred for about 30 minutes to obtain a mixture. The coating agent solution had a mass concentration of 5.00%. The mixture was fused and dried at 200°C for about 12 hours. The dried sample was transferred to a carbonization furnace for carbonization; in a protective atmosphere, the temperature was increased at a rate of 20°C / min and kept at 1300°C for 15 hours; a modified coated negative electrode active material was obtained. See Table 1 for details.
[0223] 2. Forming the negative electrode sheet
[0224] The obtained negative electrode active material powder was mixed with thickener (carboxymethyl cellulose), binder (SBR), and conductive agent in a mass ratio of 97.3:1.2:0.8:0.7, and mixed with solvent (deionized water) in a vacuum mixer to prepare negative electrode slurry, which was then evenly coated on the negative electrode current collector copper foil, and the negative electrode current collector coated with the negative electrode slurry was dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain negative electrode sheets. Specific parameters are shown in Table 1.
[0225]
Electrolyte preparation
[0226] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then the fully dried lithium salt LiPF 6 It is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0227]
Isolation film
[0228] Choose 12 micron polyethylene film.
[0229]
Battery assembly
[0230] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion secondary battery is obtained.
[0231] Embodiment 2-8
[0232] The differences from Example 1 are detailed in Table 1 and Table 2, and the rest are the same.
[0233] Comparative Example 1
[0234] The difference from Example 1 is the preparation of the negative electrode sheet. The negative electrode sheet of this comparative example is prepared as follows:
[0235] The negative electrode active material powder (graphite) is mixed with a thickener (carboxymethyl cellulose), a binder (SBR), and a conductive agent in a mass ratio of 97.3:1.2:0.8:0.7, and mixed with a solvent (deionized water) in a vacuum mixer to prepare a negative electrode slurry, which is then evenly coated on the negative electrode current collector copper foil. The negative electrode current collector coated with the negative electrode slurry is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode sheet. Specific parameters are shown in Table 1.
[0236] Comparative Example 2
[0237] The difference from Example 1 lies in the preparation of the negative electrode active material. The negative electrode active material of this comparative example is prepared as follows:
[0238] The asphalt (unoxidized) is heated to 100 to 120°C, sodium dodecyl sulfate (SDS) is dissolved in water, the water temperature is maintained at 60°C, and the heated oxidized asphalt is slowly added to the surfactant aqueous solution under high-speed stirring at 3000 rpm, and stirred for 10 minutes to obtain a coating agent solution. The concentration of the surfactant is 1% of the total mass of the oxidized asphalt.
[0239] The coating agent solution and the core (graphite) were mixed at room temperature and stirred for about 30 minutes to obtain a mixture. The coating agent solution had a mass concentration of 5.00%. The mixture was fused and dried at 200°C for about 12 hours. The dried sample was transferred to a carbonization furnace for carbonization; in a protective atmosphere, the temperature was increased at a rate of 20°C / min and kept at 1300°C for 15 hours; a modified coated negative electrode active material was obtained. See Table 1 for details.
[0240]
Performance test
[0241] Performance tests of various examples and comparative examples:
[0242] 1. Performance test of negative electrode active materials
[0243] (1) Oxygen bonding test (XPS test):
[0244] The negative electrode active material samples prepared in this experiment were processed to ensure that their surfaces were clean and free of contamination. The samples were placed in an ultra-high vacuum environment to prevent molecules in the air from interfering with the test results. Then, high-energy X-rays (1486.6 eV aluminum Kα radiation) were irradiated to the sample surface to excite the electrons on the sample surface, and their kinetic energy was captured and recorded by the detector. By analyzing the kinetic energy distribution of these photoelectrons, the bonding mode of each oxygen element and C on the sample surface was determined.
[0245] (2) Existence state and relative content of oxygen element (FTIR):
[0246] The sample is mixed with potassium bromide and pressed into a tablet. The absorption characteristics of the sample in the infrared region are scanned using an FTIR spectrometer to identify and analyze the characteristic peaks of oxygen-containing groups, thereby indirectly inferring the presence of oxygen and estimating its relative content.
[0247] (3) Characterization of the disorder of finished products - Raman test: Raman parameters R50, (R90-R10) / R50 and X of active materials in the active material layer.
[0248] The high-precision Renishaw confocal Raman testing equipment is used to perform an all-round scan of the material surface. The scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500. The Raman spectra at different positions on the material surface are measured, and the corresponding ID / IG values are obtained. The selected median, distribution and proportion of the uncovered part are obtained, namely R50, (R90-R10) / R50 and X.
[0249] The meaning and selection method of R50 / 90 / 10:
[0250] The corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large. The Raman value corresponding to the 10% ranking is defined as R10, the Raman value corresponding to the 50% ranking is defined as R50 (Raman median), and the Raman value corresponding to the 90% ranking is defined as R90.
[0251] X selection method:
[0252] The surface of the negative electrode active material was scanned in all directions using high-precision Renishaw confocal Raman testing equipment. The scanning area was 100*100 microns, the step length was 2 microns, and the total number of scanning points was 2500. The Raman values ID / IG corresponding to the 2500 scanned points were calculated, and the proportion of ID / IG≤0.1 in the total number of measurements was counted.
[0253] 2. Battery performance test
[0254] (1) Fast charging capability test: The batteries of the above-mentioned embodiments and comparative examples were charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically comprising: at 35°C, the batteries were charged at a constant current of 1C to a voltage of 4.4V, then charged at a constant voltage to a current of ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to a voltage of 2.8V, and the actual capacity was recorded as C0. Then the battery is charged with constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, 5C0 in sequence to the full battery charge cut-off voltage of 4.4V or 0V negative electrode cut-off potential (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to the full battery discharge cut-off voltage of 2.8V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80% Charge, when "SOC = 0" means the battery is fully discharged, when "SOC = 100%" means the battery is fully charged) the corresponding negative electrode potential, draw the charging rate negative electrode potential curve under different SOC states, and obtain the charging rate corresponding to the negative electrode potential of 0V under different SOC states after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C 40% SOC, C50% SOC, C60% SOC, C70% SOC, C80% SOC, according to the formula (60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%, the charging time T of the battery from 10% SOC to 80% SOC is calculated in min. The shorter the time, the better the fast charging performance of the battery.
[0255] (2) Fast charge cycle life: Step charge is performed at the charging rate at each SOC obtained from the fast charge capability test, C10%SOC CC to 10%SOC, C20%SOC CC to 20%SOC, C30%SOC CC to 30%SOC, C40%SOCCC to 40%SOC, C50%SOC CC to50%SOC, C60%SOC CC to 60%SOC, C70%SOC CC to70%SOC, C80%SOC CC to 80%SOC, 0.33C to 100%SOC, 0.33C DC to 2.5V, and the number of cycles when the battery decays to 80%SOH is recorded.
[0256] The performance test results of various embodiments and comparative examples are shown in Table 2 and Table 3.
[0257] Table 1 Negative electrode active material preparation process
[0258]
[0259]
[0260] Table 2 Performance parameters of negative electrode active materials
[0261]
[0262] Table 3 Battery performance data
[0263]
[0264] From the above table data, we can see that:
[0265] Compared with Comparative Examples 1 and 2, the charging time T of the battery at 25°C from 10% SOC to 80% SOC is much longer than the charging time of each embodiment. This shows that the solutions of Comparative Examples 1 and 2 have very limited improvement on the fast charging performance of the battery. However, the solutions of each embodiment of the present application can effectively shorten the charging time and improve the fast charging performance of the battery.
[0266] Furthermore, compared with Comparative Examples 1 and 2, the embodiment of the present application has less impact on the cycle performance; therefore, the solution of the present application can improve the fast charging performance while taking into account the cycle performance.
[0267] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A battery cell, characterized in that: include: A negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode film layer; The negative electrode film layer includes a negative electrode active material; the negative electrode active material includes a core and a coating layer; The core is graphite; the coating layer includes carbon and oxygen-containing functional groups; In the negative electrode active material, the content of the oxygen-containing functional group is 20% to 70% by mass.
2. The battery cell according to claim 1, characterized in that: In the negative electrode active material, the content of the oxygen-containing functional group is 22% to 52% by mass.
3. The battery cell according to claim 1 or 2, characterized in that: The oxygen-containing functional group includes at least one of a hydroxyl group, a carbonyl group, a carboxyl group or an epoxy group.
4. The battery cell according to any one of claims 1 to 3, characterized in that: The negative electrode active material has an oxygen content of 0.2% to 1% by mass; Optionally, in the negative electrode active material, the oxygen content is 0.57%-0.77% by mass.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The median of the Raman value ID / IG of the negative electrode active material is denoted as R 50 ; said R 50 is 0.15 to 0.40; 50 The testing method is as follows: use a high-precision Renishaw confocal Raman testing device to perform an all-round scan on the surface of the negative electrode active material, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, and the Raman value ID / IG corresponding to the 50% ranking is defined as R50.
6. The battery cell according to any one of claims 1 to 5, characterized in that: The Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; the (R90-R10) / R50 is 0.13-0.25; the testing method of R90, R10 and R50 is: use a high-precision Renishaw confocal Raman testing device to perform an all-round scan on the surface of the negative electrode active material, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the Raman values ID / IG corresponding to the 2500 scanned points are arranged from small to large, the Raman value ID / IG corresponding to the 10% ranking is defined as R10, the Raman value ID / IG corresponding to the 50% ranking is defined as R50, and the Raman value ID / IG corresponding to the 90% ranking is defined as R90.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as an uncoated portion; Based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; and X is 3.22% to 10%.
8. A negative electrode active material, characterized in that: The negative electrode active material comprises a core and a coating layer; The inner core is graphite; the coating layer comprises carbon and oxygen-containing functional groups; in the negative electrode active material, the content of the oxygen-containing functional groups is 20% to 70% by mass.
9. The negative electrode active material according to claim 8, characterized in that The negative electrode active material satisfies at least one of the following characteristics: (1) In the negative electrode active material, the content of the oxygen-containing functional group is 0.22% to 0.52% by mass; (2) In the coating layer, the oxygen-containing functional group includes at least one of a hydroxyl group, a carbonyl group, a carboxyl group or an epoxy group; (3) The negative electrode active material has an oxygen content of 0.2% to 1% by mass; (4) The median of the Raman value ID / IG of the kernel is denoted as R 50 ; R of the kernel 50 is 0.06 to 0.1; the R50 test method of the kernel is: use a high-precision Renishaw confocal Raman test device to perform an all-round scan on the material surface, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% sorting is defined as R50; (5) The median of the Raman value ID / IG of the negative electrode active material is denoted as R 50 ; R of the negative electrode active material 50 is 0.15-0.40; the R50 test method is: use a high-precision Renishaw confocal Raman test device to perform an all-round scan on the material surface, with a scanning area of 100*100 microns, a step length of 2 microns, and a total of 2500 scanning points; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 50% sorting is defined as R50; (6) The Raman value ID / IG distribution of the negative electrode active material is recorded as (R90-R10) / R50; the (R90-R10) / R50 is 0.13-0.25; the test method of R90, R10 and R50 is: use a high-precision Renishaw confocal Raman test device to perform a full-scale scan of the material surface, the scanning area is 100*100 microns, the step length is 2 microns, and the total number of scanning points is 2500; the corresponding Raman data obtained by scanning 2500 points on the material surface are arranged from small to large, and the Raman value corresponding to the 10% ranking is defined as R10, the Raman value corresponding to the 50% ranking is defined as R50, and the Raman value corresponding to the 90% ranking is defined as R90; (7) The portion of the negative electrode active material with a Raman value ID / IG≤0.1 is recorded as the uncoated portion; based on the total surface area of the negative electrode active material, the proportion of the uncoated portion of the negative electrode active material is recorded as X; and X is 3.22% to 10%.
10. A method for preparing a negative electrode active material, characterized in that: include: A coating agent containing oxygen-containing functional groups and a core are prepared into a mixed solution; Carbonizing the mixed solution to form a coating layer; The core is graphite; the coating layer includes carbon and oxygen-containing functional groups; In terms of mass percentage, the content of the oxygen-containing functional group is 20% to 70% of the total mass of the coating layer and the core.
11. The method for preparing the negative electrode active material according to claim 10, characterized in that: Based on the total mass of the coating agent, the content of the oxygen-containing functional groups in the coating agent containing oxygen-containing functional groups is 1%-5%.
12. The method for preparing a negative electrode active material according to claim 10 or 11, characterized in that: The preparation of a capping agent containing an oxygen-containing functional group comprises: Using an oxidant to react with a carbon coating agent; Optionally, the oxidant includes: at least one of an acidic substance or an alkaline substance; Optionally, the acidic substance includes: at least one of nitric acid, sulfuric acid, hydrogen peroxide or potassium permanganate; Optionally, the alkaline substance includes: at least one of sodium hydroxide or potassium hydroxide; Optionally, the carbon coating agent includes: a copolymer or an organic polymer composite material; Optionally, the carbon coating agent includes: at least one of asphalt, sucrose or glucose; Optionally, the content of the oxidant is 1% to 10% of the mass of the carbon coating agent.
13. The method for preparing a negative electrode active material according to any one of claims 10 to 12, characterized in that: The method of preparing a mixed solution of a coating agent containing oxygen-containing functional groups and a core comprises: mixing a carbon coating agent solution with the core; Optionally, preparing the carbon coating agent solution comprises: Mixing a surfactant, water and the carbon coating agent at 50° C. to 60° C.; Optionally, the surfactant includes: anionic surfactant; Optionally, the surfactant includes: sodium dodecyl sulfate.
14. The method for preparing a negative electrode active material according to any one of claims 10 to 13, characterized in that: The step of carbonizing the mixed solution comprises: When the coating agent solution is mixed with the core, the concentration of the coating agent solution is 1% to 10% by mass percentage; Optionally, the carbonization temperature is 700°C to 1300°C.
15. The method for preparing a negative electrode active material according to any one of claims 10 to 14, characterized in that: The preparation method further comprises: The product obtained by carbonization is subjected to oxidation treatment; Optionally, the oxidation treatment includes: reacting the product obtained by carbonization with an oxidant.
16. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 7.
17. An electrical device, characterized in that: The electrical device comprises the battery according to claim 16.
Citation Information
Patent Citations
Graphite-based negative electrode active material, preparation method and application thereof, and secondary battery
CN115312731A
Graphite oxide composite material, high-energy-density fast-charging negative plate, preparation method and lithium ion battery
CN116864680A
Modified graphite and preparation method thereof, carbon-coated negative electrode active material and preparation method thereof, negative electrode plate, secondary battery, battery module, battery pack and electric device
CN116964782A
Battery cell, battery device, and electric device
CN119133577A
Battery cell, battery device, and electric device
CN119153758A